Coumarin-1,2,3-Triazole Hybrids as Promising Antibacterial Agents: In silico Molecular Docking, ADMET and Molecular Dynamics Simulation Studies (Exploring in silico Antibacterial Potential of Coumarin-1,2,3-triazoles) - Mishra, Krishna Narayan; Rashmi, Mayank; Upadhyay, Harish Chandra (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: A lot of coumarin-1,2,3-triazole hybrids have been reported to show antibacterial activities, but most of them are unexplored in clinical studies. Herein, we wish to apply in silico docking, physiochemical predictions and molecular dynamics simulation studies on coumarin-1,2,3-triazole hybrids to explore their successful transformation in to broad spectrum antibacterial agent for clinical use. Materials and Methods: A library of 196 compounds with the coumarin-1,2,3-triazole motif showing antibacterial activity against various pathogenic bacteria was generated, and molecules were in silico screened for their binding affinities through molecular docking against six antibacterial targets Dihydropteroate synthase (PDB, ID:1TX2), Penicillin-binding protein-3 (PDB, ID:3OCN), DNA Gyrase-B24 (PDB, ID:6YD9), UDP-N- Acetylglucosamine enolpyruvyl transferase (PDB, ID:1 UAE), Sortase A (PDB, ID:2MLM), and Dethiobiotin synthetase (PDB, ID:4WOP) using AutoDock Vina. On the basis of high docking score and suitable physiochemical and ADMET parameters hybrids 134, 143, 174, and 176 were subjected to 100 ns of Molecular Dynamics (MD) on GROMACS to investigate the protein-ligand complex’s stability. Results: All the coumarin-1,2,3-triazole hybrids docked well with the target antibacterial protein and most of them exhibited higher binding affinity than the co-crystallized ligands of the respective proteins. MD simulation results in terms of Root Mean Square Deviation (RMSD), Root Mean Square Fluctuation (RMSF), Radius of gyration (Rg) and distribution of hydrogen bonds were in complete agreement of docking scores indicating for stable ligand-target bonding. Conclusion: This study provides strong evidence for coumarin-1,2,3-triazole hybrids to be excellent antibacterial agents effective on both Gram-positive and Gram-negative pathogenic strains and hybrid 176 may be considered the best out of all.
Keywords: Coumarin-1,2,3-triazoles; antibacterial; docking Extract; Molecular Dynamics; ADMET; Drug resistance